Level of physical exercises' mastering in structure of 11-13 yrs age boys' motor fitness - O.V. Ivashchenko; S.S. Iermakov; O.M. Khudolii; Marian Cretu; Vladimir Potop (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Purpose: to find the place of physical exercises' mastering level in structure of 11-13 yrs age boys' motor fitness. Material: in the research 11 yrs age boys (n=58), 12 (n=76) and 13 years age (n=93) participated. Testing program included well-known tests: "Forward roll", "Backward roll", "Vault", "Climbing rope (three attempts)", "Bridge", "Stance on shoulder blades". Results: By indicators of physical condition 11-13 yrs age boys statistically confidently differ one from another (р<0,001). Level of mastering of gymnastic exercises "Backward roll", "Vault", "Climbing rope (three attempts)", "Bridge", "Stance on shoulder blades" with age statistically confidently increases (р<0,001). Conclusions: In factorial structure of motor fitness, level of physical exercises' mastering has weight 17,5% (11 yrs age), 36,6% (12 years), 28,5% (13 years). Analysis of communities showed that in 11-13 yrs age boys training of motor abilities is effective (if they become a component of mastered motor skills).